Legal Perspective on the Credit Restructuring Program as an Effort to Accelerate the Recovery of the Business Sector Post the COVID-19 Pandemic - Widianto, Bayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The COVID-19 virus outbreak Indonesia has created problems very significant impact sustainability of MSMEs in Indonesia, and that is turned out to have impact on decline in MSME sector. To overcome the problems caused by COVID-19, government has issued various policies, one of which is restructuring of the COVID-19 stimulus credit stipulated in Financial Services Authority Regulation. This study aims to determine implementation and impact of credit restructuring policies on MSME debtors. Research is normative-empirical juridical type and descriptive in nature. Data in this study consisted of primary and secondary data. Data collection instruments in this study were divided into two, namely primary and secondary data. Primary data was collected by interview method, while secondary data collection used documentation study. This study uses qualitative analysis techniques. Goal of this research is to analyze the effectiveness of credit restructuring program in supporting economic recovery after COVID-19 pandemic.